Brain tumor detection and classification: A framework of marker‐based watershed algorithm and multilevel priority features selection. Issue 6 (23rd February 2019) - Khan, Muhammad A.; Lali, Ikram U.; Rehman, Amjad; Ishaq, Mubashar; Sharif, Muhammad; Saba, Tanzila; Zahoor, Saliha; Akram, Tallha
Abstract: Brain tumor identification using magnetic resonance images (MRI) is an important research domain in the field of medical imaging. Use of computerized techniques helps the doctors for the diagnosis and treatment against brain cancer. In this article, an automated system is developed for tumor extraction and classification from MRI. It is based on marker‐based watershed segmentation and features selection. Five primary steps are involved in the proposed system including tumor contrast, tumor extraction, multimodel features extraction, features selection, and classification. A gamma contrast stretching approach is implemented to improve the contrast of a tumor. Then, segmentation is done using marker‐based watershed algorithm. Shape, texture, and point features are extracted in the next step and high ranked 70% features are only selected through chi‐square max conditional priority features approach. In the later step, selected features are fused using a serial‐based concatenation method before classifying using support vector machine. All the experiments are performed on three data sets including Harvard, BRATS 2013, and privately collected MR images data set. Simulation results clearly reveal that the proposed system outperforms existing methods with greater precision and accuracy. Abstract : An automated system is proposed for tumor extraction and classification based on marker‐based watershed segmentation, features selection. The system includes tumor contrast, tumor extraction, multimodel features extraction, selection and classification.